Biological targets of cholinergic pesticides and possible use of alternative models for toxicity testing - C. Falugi; Z. Rakonczay; M.G. Aluigi (Journal of Biological Research, 2011)
The use of protection plant products for the control of pests in agriculture should be accompanied by a clear understanding of possible damages to human and environmental health. The mechanisms of action and the affects on developing organisms exerted by acute and chronic exposure to the main classes of cholinergic pesticides are reviewed.